P.039 Generating choosing wisely Canada recommendations for neurology. (5th June 2019) - Beyak, C; Costello, F; Couillard, P
Abstract : Background: Many guidelines in neurology encompass the principles of Choosing Wisely Canada (CWC): resource stewardship, patient safety, and high value care. There are currently 49 medical societies with CWC recommendations excluding the Canadian Neurologic Society (CNS).Methods: A descriptive process for list generation is outlined. A review of the American Choosing Wisely recommendations was undertaken to generate an adapted list of ten recommendations. CNS board members vetted this list and an online survey was sent to each CNS member.Results: A short list of recommendations endorsed by the CNS membership at large will be presented according to the survey results. CWC promotion of the list will take place to reach specialists, primary care providers, and trainees to ensure high value neurological care delivery is the standard across Canada.Conclusions: The process to delineate CWC recommendations for neurology is outlined. Participating in the CWC movement is an important leadership initiative for the CNS. It demonstrates the commitment of Canadian neurologists to the principles of high value patient care in neurology.